Новые находки печатей эпохи бронзы с Низовий Мургаба - Масимов, И. С.
Masimov, I. S.; New Finds of Bronze Age Seals from the Lower Murgab; Engl. Résumé; südturkmen. Siegelzylinder, Vergleich mit Vorderasien.